2022
DOI: 10.1007/s10055-022-00667-x
|View full text |Cite
|
Sign up to set email alerts
|

The virtualization of human–robot interactions: a user-centric workload assessment

Abstract: Interest in the virtualization of human–robot interactions is increasing, yet the impact that collaborating with either virtual or physical robots has on the human operator’s mental state is still insufficiently studied. In the present work, we aimed to fill this gap by conducting a systematic assessment of a human–robot collaborative framework from a user-centric perspective. Mental workload was measured in participants working in synergistic co-operation with a physical and a virtual collaborative robot (cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Participants physically touched the virtual robot and moved their arms to relocate it over the worktable. In line with our previous findings [12], the actions performed concurrently with the arithmetic task were categorized under high workload. Differently, when performed without any additional task, they were categorized under the low workload.…”
Section: ) Actionssupporting
confidence: 83%
See 4 more Smart Citations
“…Participants physically touched the virtual robot and moved their arms to relocate it over the worktable. In line with our previous findings [12], the actions performed concurrently with the arithmetic task were categorized under high workload. Differently, when performed without any additional task, they were categorized under the low workload.…”
Section: ) Actionssupporting
confidence: 83%
“…As a first contribution, we introduce a general profiling framework applicable to different virtual devices (e.g., VR, AR), applied fields (e.g., everyday use cases, work scenarios), and types of user behaviors (e.g., walking, searching, pointing). We test our framework on data from our previous works [11], [12], showing the generability of the approach. Since such previous studies revealed gender differences under diverse workload conditions, we additionally investigate the workload impact on profiling.…”
Section: A Contributionsmentioning
confidence: 93%
See 3 more Smart Citations